2017
DOI: 10.1038/srep46218
|View full text |Cite
|
Sign up to set email alerts
|

An Intrathermocline Eddy and a tropical cyclone in the Bay of Bengal

Abstract: The Bay of Bengal, subjected to monsoonal forcing and tropical cyclones, displays a complex field of ocean eddies. On 5 December 2013 a sub-surface vortex or Intrathermocline Eddy (ITE) composed of water characteristic of the Andaman Sea was observed within the thermocline of the western Bay of Bengal. We propose that the ITE was the product of Tropical Cyclone Lehar interaction on 27 November 2013 with a westward propagating surface eddy from the eastern Bay of Bengal. While Lehar’s interaction with the ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
2
39
2
Order By: Relevance
“…Gordon et al () noticed intrathermocline eddy at subsurface depths with the water characteristics of Andaman Sea in the western BoB and suggested that eastern BoB and Andaman Sea provides the source waters for eddies in the BoB. All six sampled ACEs were originated in the eastern BoB (Figure ) and advected to the west.…”
Section: Resultsmentioning
confidence: 95%
“…Gordon et al () noticed intrathermocline eddy at subsurface depths with the water characteristics of Andaman Sea in the western BoB and suggested that eastern BoB and Andaman Sea provides the source waters for eddies in the BoB. All six sampled ACEs were originated in the eastern BoB (Figure ) and advected to the west.…”
Section: Resultsmentioning
confidence: 95%
“…Takikawa et al (2005) detected SSE to the southeast of the Ryukyu Islands, which had thickness and width of 300 m and 100 km, respectively. In December 2013, a subsurface lens of water from the Andaman Sea was captured in the Bay of Bengal (Gordon et al 2017). Nan et al (2017) detected an extra-large subsurface anticyclonic eddy with horizontal scale of 470 km in the Northwest Pacific subtropical gyre.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proven that SSE can strongly influence intermediate or deeper ocean layers by affecting the subsurface circulation, pathways of water masses, and redistribution of heat, salt, and momentum (Andrade et al 2014;Colas et al 2012;Nan et al 2017;Pelland et al 2013). Unlike surface eddies (SEs), which can be characterized using satellite altimeter data, SSEs have weak surface expression, and they are poorly understood because of the lack of their systematic measurement (Chaigneau et al 2011;Gordon et al 2017;Johnson and McTaggart 2010). Most reported eddies have survived for a significant time (of the order of months) and traveled considerable distance (hundreds of kilometers) (Combes et al 2015;Takikawa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al () detected two, southwest‐slanted, eddy pathways in the BoB: one located near the western boundary and the other in the central Bay (central pathway). Recently, Gordon et al () reported the existence of intrathermocline anticyclonic eddy at the subsurface depths in the central BoB, which represents the dominate influence of vertical motion of thermocline.…”
Section: Introductionmentioning
confidence: 99%